Analisis Faktor Yang Mempengaruhi Hasil Belajar Menggunakan E-Learning Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Novia Ayu Nengsih; Rani Sofya (Universitas Negeri Padang, 2023)
This study aims to analyze the factors that influence learning outcomes using e-learning on students of the Faculty of Economics, Padang State University. Factors that affect learning outcomes consist of internal factors and external factors. The type of research is descriptive quantitative research. The sampling technique in this study is proportional random sampling, this technique is used when the population has members or elements that are not homogeneous. The number of samples in this study were 96 students of the Faculty of Economics, Padang State University in 2018, 2019 and 2020. The data used were primary data and secondary data. Data collection techniques in the form of a questionnaire. The analytical method used is descriptive analysis and factor analysis. Based on the result of factors analysis, there are four factots that influence learning outcomes using e-learning on students of the Faculty of Economics, Padang State University, namely instrumental factors, family factors, psychological factors and physiological factors. The dominant factor that affects learning outcomes using e-learning on students of the Faculty of Economics, Padang State University is the instrumental factor. For students, in order to understand the material given by the lecturer in e-learning. For lectuterer to be able to explain the material provided in e-learning to the maximum so that students can obtain satisfactory learning outcomes.